Doping core–shell nanoparticles into a solution-processed electron transporting layer for polymer light-emitting diodes. Issue 44 (18th April 2016) - Peng, Jinghong; Tang, Fu; Xu, Xinjun; Jia, Manping; Li, Lidong
Abstract : Core–shell gold nanoparticles have been doped into the solution-processed electron-transporting layer of PLED to obtain enhanced EL performance. Abstract : Core–shell gold nanoparticles have been doped into the solution-processed electron-transporting layer (ETL) of polymer light-emitting diodes (PLEDs). By using this doping strategy, metal-enhanced fluorescence was realized in the device. The doped device has obtained enhanced luminance, enhanced luminous efficiency and a reduced turn-on voltage compared with that using the non-doped ETL.